The book of Amos - Carroll R., M. Daniel, 1953- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2020)
"A commentary on the book of Amos, combining a detailed reading of the Hebrew text with an eye to its historical background and current relevance"--
Includes bibliographical references and indexes.
Keywords: Bible -- Commentaries; Bible. -- Criticism, Textual